Literature Review : Strategi Inovatif dalam Pembelajaran IPA SMP untuk Peningkatan Hasil Belajar - Angelina Dina Lestari; Ernita Vika Aulia; Muhamad Arif Mahdiannur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Low science learning outcomes at the junior high school level are a major problem caused by the dominance of conventional, teacher-centered teaching methods. The purpose of this study is to examine various innovative learning strategies, how effective they are, and their impact on student learning outcomes. The literature review method was used to review national and international articles published between 2020 and 2025 that discuss the application of innovation-based learning strategies in science. The strategy patterns, implementation effectiveness, and their impact on student learning outcomes were analysed using content analysis techniques. The research findings indicate that strategies such as problem-based learning (PBL), project-based learning (PjBL), discovery learning, environmental-based learning, and cooperative learning using the Think-Pair-Share (TPS) method are effective in increasing students' motivation and activity, as well as their learning outcomes in the cognitive, affective, and psychomotor domains. Generally speaking, the strategies are all student-centered. This is demonstrated by the constructivist approach, which emphasises contextual and collaborative learning. The results of this study indicate that implementing a creative learning approach can be an effective way to improve the quality of science learning and student learning outcomes in junior high school.